(untitled) (Вісник: Міжнародні відносини, 2024)
Purpose. The purpose of the study is to research how digital policy regarding the development of technology and its regulation becomes a source of influence and strength in the imeplementation of foreign policy priorities and to design the recommendations for strengthening foreign policy priorities of Ukraine during the war with the modernized approach to conduct of digital diplomacy. Results. It is important for Ukraine to update the strategy and goals of digital diplomacy without limiting it to only one direction of public diplomacy. Ukraine needs to establish closer coordination and cooperation between the Ministry of Digital Transformation and the Ministry of Foreign Affairs of Ukraine. Ukraine’s progress in digital transformations should be used not as a communication message, but as a leverage of influence that should be integrated into the work of diplomats while builsing bilateral and multilateral cooperation. Ukraine should take into account EU approaches to digital diplomacy. Technological solutions of Ukraine are in many aspects breakthrough, which gives the country the opportunity not only to adopt standards from others, but also to spread its own. Ukraine should begin to become more actively involved in international cooperation platforms in the field of digital technologies, in order to strengthen its digital resilience and capabilities in the war with Russia and at the same time weaken the enemy’s position. In this regard, the EU and the USA are key partners with whom permanent and systematic cooperation should be built both at the bilateral level with governments, business communities and civil society, and at the international level. Scientific novelty. Research into the geopolitics of technology as an integral part of understanding relations between states at the international level has gained further development and conceptalisation. Digital technologies are influencing global politics, becoming a source of power and leverage at both the bilateral and multilateral levels. Practical value. For Ukraine, the issue of digitization actively arose after 2019, but the benefits of digital transformation became especially tangible with the full-scale invasion of the Russian Federation of Ukraine. Digital services at DIIA, development of digital infrastructure and cyber security are the pillars of Ukraine’s resilience in the information war. Moreover, Ukraine actively began to talk about its achievements and became an example of such resilience, engaging in a dialogue on cooperation with the European Union and the United States. This research is valuable and relevant in terms of how technology and its regulation can be used to exert external influence and build bilateral and multilateral relations, while competition for influence and the spread of democratic principles in the technology governance are key to overcoming autocratic and totalitarian approaches. promoted by Russia and other countries.